Electrochemical capacitance spectroscopy and capacitive relaxation of the changeover process in iron hexacyanoferrate molecular compound - Bueno, Paulo Roberto [UNESP]; Gimenez-Romero, David; Ferreira, Fabio Furlan; Setti, Grazielle Oliveira [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
In this work it was proposed the use electrochemical capacitance spectroscopy (ECS) to evaluate the storage process during changeover in FeHCF compound. The approach is equivalent to electrochemical impedance spectroscopy (EIS) albeit from such analysis it was possible to focus attention on the capacitive and dielectric relaxation instead of the dispersive relaxation related to charge transfer. From such approach it was possible to obtain complementary information on the role played by [Fe(2+)(CN)(6)](4-) vacancies during the changeover process. It was observed that Fe(3+)(NC)(5)OH(-) clusters located in these vacancies mediate an electronic and ionic coupled trapping/detrapping process giving rise to what was considered an electrochemical dipolar relaxation whose K(+) ionic specie with Fe(3+)(NC)(5)OH(-) clusters are the key entities in controlling the general process. The capacitive response reaches its maximum value at the changeover due to saturation of the electronic occupation at Fe(3+)(NC)(5)OH(-) clusters. The nature and the dynamics of the capacitive relaxation process were either discussed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Impedance spectroscopy; Capacitance spectroscopy; Changeover; Molecular compounds; Hexacyanoferrates; Prussian Blue